First reported case of de Novo claes-jensen syndrome (CJS) in Palestine: diagnostic challenges and genetic insights - Manal M. Shaheen; Ramzi H. Mujahed; Saja E. Abusabha; Iman M. Alwahsh; Areen A. Abufara; Leen J. Junaidi; Haya A. Alkablan (BMC Pediatrics)
Abstract Background Claes-Jensen syndrome (CJS) is a rare X-linked intellectual disability caused by mutations in the KDM5C gene, encoding a histone demethylase involved in chromatin remodeling and neurodevelopment. Males with hemizygous mutations in KDM5C present with intellectual disability, dysmorphism, and neurodevelopmental delays. Mutations, either maternally transmitted or de novo, account for 0.7-2.8% of X-linked intellectual impairments. This case reports a rare de novo variant in the KDM5C gene in a Palestinian male patient, contributing to the limited literature on this condition. Case presentation We present a 2-year and 10-month-old Palestinian male with developmental regression following an acute viral illness at 22 months. This included the loss of the ability to walk, developmental delays, and persistently elevated lactic acid. Genetic testing, including trio-based whole-exome sequencing, identified a de novo KDM5C mutation (c.2827 C > T p.Arg943), confirming the diagnosis of Claes-Jensen syndrome. Neuroimaging showed faint hyperintensities in the posterior periventricular white matter, suggestive of dysmyelination. Conclusion This case highlights the diagnostic challenges of CJS and the importance of genetic testing in neurodevelopmental disorders. Early recognition aids in symptomatic management and improves clinical understanding of this rare condition. Our report adds new insight into the clinical spectrum of CJS and emphasizes the need for heightened awareness among clinicians.